Beyond passive observation: feedback anticipation and observation activate the mirror system in virtual finger movement control via P300-BCI - Syrov, Nikolay; Yakovlev, Lev; Miroshnikov, Andrei; Kaplan, Alexander (Frontiers in Human Neuroscience, 2023)
Action observation (AO) is widely used as a post-stroke therapy to activate sensorimotor circuits through the mirror neuron system. However, passive observation is often considered to be less effective and less interactive than goal-directed movement observation, leading to the suggestion that observation of goal-directed actions may have stronger therapeutic potential, as goal-directed AO has been shown to activate mechanisms for monitoring action errors. Some studies have also suggested the use of AO as a form of BCI feedback. In this study, we investigated the potential for observation of virtual hand movements within a P300-based brain-computer interface as a feedback system to activate the mirror neuron system. We also explored the role of feedback anticipation and estimation mechanisms during movement observation. By analyzing event-related desynchronization and synchronization (ERD/S) of sensorimotor EEG rhythms and Error-related Potentials (ErrPs), we traced the cortical activity of 20 healthy subjects during observation of virtual hand finger flexion presented as feedback in the P300-BCI loop and compared the dynamics of ERD/S and ErrPs during observation of correct feedback and errors. We also analyzed these EEG markers during passive AO under two conditions: when subjects anticipated the action demonstration and when the action was unexpected. A pre-action mu-ERD was found both before passive AO and during action anticipation within the BCI loop. Furthermore, a significant increase in beta-ERS was found during AO within incorrect BCI feedback trials. We suggest that the BCI feedback may exaggerate the passive-AO effect, as it engages feedback anticipation and estimation mechanisms as well as movement error monitoring simultaneously. The results of this study provide insights into the potential of P300-BCI with AO-feedback as a tool for neurorehabilitation.